Implementasi Jaringan Hotspot Menggunakan Metode Queve Tree Pada Router Mikrotik (Studi Kasus : SMK Gita Kirtti 1 Jakarta) - Imam Maulana; Hardiansyah Hardiansyah (Institut Sains dan Teknologi Nasional, 2022)
ABSTRACT The provision of a hotspot network at Gita Kirtti 1 Jakarta Vocational School was made based on problems that often occur in the learning activity, namely unstable internet speed when accessed by many users at once. This of course can disrupt the teaching and learning process, such as when accessing learning materials in the form of videos that require a stable internet speed, so that it can allow some students to open websites that are not related to learning which of course are not related to knowledge. This research aims to provide hotspot facilities for teachers and students at schools by utilizing Mikrotik routers in schools. This.research is using Queue Tree method. The method used to limit bandwidth is more complex than using a simple queue. Queue tree serves to limit bandwidth]on]a]Mikrotik that has.more than one.internet.connections. The]results;of.this study are]the availability of]a hotspot network that can be accessed by teachers and students at several points in the school that can be used to find information related to the world of education. There are different levels of user rights restrictions between teachers and students connected to the network. It is hoped that the school can maintain the hotspot network that has been provided so;that;it;can be useful as.a support for learning at school. Keywords : Electronic Selection Applications, UCD, E-mobile Voting.